2000
DOI: 10.1021/np990463m
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cytotoxicity in a Z-Photoisomer of a Benzopyran Derivative of Propolis

Abstract: (Z)-2,2-Dimethyl-8-(3-methyl-2-butenyl)-benzopyran-6-propenoic acid (1) was isolated from Brazilian propolis, together with the known benzopyran derivative, (E)-2, 2-dimethyl-8-(3-methyl-2-butenyl)-benzopyran-6-propenoic acid (2). The structure was determined by spectroscopic analyses, which included 1D and 2D (1)H and (13)C NMR experiments, as well as MS, IR, and UV spectroscopy. Compound 2 rapidly changed to 1 under UV irradiation conditions (365 nm), and the reverse reaction was also observed. The ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Propolis samples from tropical zones, such as Brazil with its vast biodiversity, have become a subject of increasing scientific and economic attention. From Brazilian propolis, several bioactive derivatives of hydroxycinnamic, caffeoylquinic and diterpenic acids besides benzofuranes and benzopyranes have already been characterized ( 18 , 23–25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Propolis samples from tropical zones, such as Brazil with its vast biodiversity, have become a subject of increasing scientific and economic attention. From Brazilian propolis, several bioactive derivatives of hydroxycinnamic, caffeoylquinic and diterpenic acids besides benzofuranes and benzopyranes have already been characterized ( 18 , 23–25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seven compounds present in propolis from the south and southeast of Brazil have been identified by comparison of their tandem mass spectra with those of standards acquired commercially or isolated in relation to previous research: 18,21 para-coumaric acid, 3-methoxy-4-hydroxycinnamaldehyde, 2,2-dimethyl-6-carboxyethenyl-2H-1-benzopyran, 3-prenyl-4-hydroxycinnamic acid, chrysin, pinocembrin and 3,5-diprenyl-4-hydroxycinnamic acid (Table 1). These compounds have been reported previously in samples of Brazilian propolis and the activity of some of them against bacteria, 21 Trypanossoma cruzi 21 and Candida, 45 as well as their cytotoxic 46 and antioxidant 47 activities have been investigated. The ion of m/z 515 has been determined to be a deprotonated form of dicaffeoylquinic acid by comparison of its ESI-MS/MS mass spectrum (Fig.…”
Section: Structural Characterization Via Tandem Mass Spectrometrymentioning
confidence: 97%
“…3-(2,2-dimethyl-8-prenylbenzopyran-6-yl)propenoic acid (5) having cytotoxic activity was also isolated from Brazilian propolis (Matsuno et al, 1997b). Hirota et al (2000) isolated (Z)-2,2-dimethyl-8-prenyl-benzopyran-6-propenoic acid (25), a Z-photoisomer of 5, which displayed an approximately 7-fold stronger cytotoxicity against human lung carcinoma cells (HTL-2) than 5. Matsuno et al (1997cMatsuno et al ( , 1998) also reported the isolation from Brazilian propolis and cytotoxic activity of a similar compound, artepillin C (26).…”
Section: Antitumour Activitymentioning
confidence: 99%